Synthesis and characterization of partially phosphorylated poly (Vinyl Alcohol) – aluminum phosphate (PPVA – AlPO4) nanocomposite / Asmalina Mohamed Saat - Asmalina, Mohamed Saat (2016)
Partially phosphorylated polyvinyl alcohol - aluminum phosphate (PPVA-AlPO4) composite were synthesized through continuous stirring and condensation at 80 °C. Interaction of pure polyvinyl alcohol (PVA) with phosphoric acid (PA) produced partially phosphorylated poly vinyl alcohol (PPVA) and the addition of aluminum (Al) source produces a PPVA-AlPO4 composite. Fourier Transform Infrared (FTIR) and Raman spectra of PPVA confirmed the phosphate group in PPVA-AlPO4 composite. The phosphate group had bonded with aluminum at C-O-P- AlPO4, O-P-O- AlPO4 and also OH-Al. The optical properties of these PPVA and PPVA-AlPO4 nanocomposite samples were examined by UV-visible and photoluminescence (PL) spectroscopy. UV analysis of PPVA shows single peak at 274 nm while in PPVA-AlPO4, the peak was shifted to lower wavenumber of 208 nm. PL spectra of PPVA-AlPO4 shows broad peak at range of 304-371, 450-550 and 560-700 nm. This confirmed that the phosphate group in PPVA created bonding with aluminum. Transgravimetric (TGA) analysis shows that the weight residue of PPVA-AlPO4 composite was higher than PPVA and PVA. X-ray diffraction (XRD) pattern of PVA shows a single peak at angle of 20°. However, the peak become broadened as PA added. Meanwhile, the addition of aluminum source produced multiple peaks referring to the multiple phases of AlPO4 in the nanocomposite. Field Emission Scanning Electron Microscopy (FESEM) confirmed the existence of multiple geometrical phases and nanosize of spherical particles. The influence of important synthesis parameters such as, effect of PPVA, effect of aluminum sources, pH and crystallization time are also studied.